Reorganising power in Indonesia : the politics of oligarchy in an age of markets - Robison, Richard, 1943- (RoutledgeCurzon/City University of Hong Kong South East Asian studies, 2004)
A new and distinctive analysis of the dramatic fall of Soeharto, the last of the great Cold-War capitalist dictators, and of the struggles that reshape the institutions and systems of power and wealth in Indonesia.